2016
DOI: 10.1369/0022155416673979
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Platelet-Derived Growth Factor Receptor Alpha Antibody Specificity May Impact Clinical Utility of Immunohistochemistry Assays

Abstract: Aberrant regulation of the receptor tyrosine kinase platelet-derived growth factor alpha (PDGFRα) is implicated in several types of cancer. Inhibition of the PDGFRα pathway may be a beneficial therapy, and detection of PDGFRα in tumor biopsies may lead to insights about which patients respond to therapy. Exploratory or clinical biomarker use of PDGFRα IHC has been frequently reported, often with polyclonal antibody sc-338. An sc-338-based assay was systematically compared with anti-PDGFRα rabbit monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…These data are suggestive of potential alterations in the tumor transcriptome when cultured or propagated outside of its native environment and are reminiscent of a previous report describing changes in the epigenome and transcriptome of mammalian cells isolated from primary tissues upon exposure to cell culture (43). Furthermore, a recent study demonstrated that an anti-PDGFRa polyclonal antibody frequently used in previous IHC analyses cross-reacts with PDGFRb, further confounding previous reports regarding the prevalence of PDGFRa expression in pediatric bone and soft tissue tumor patient samples (44). In light of this discordance in receptor expression between available preclinical bioresources and clinical specimens, it is difficult to investigate the full range of olaratumab activity in pediatric sarcoma in a preclinical setting and to identify potential predictive biomarkers.…”
Section: Discussionmentioning
confidence: 87%
“…These data are suggestive of potential alterations in the tumor transcriptome when cultured or propagated outside of its native environment and are reminiscent of a previous report describing changes in the epigenome and transcriptome of mammalian cells isolated from primary tissues upon exposure to cell culture (43). Furthermore, a recent study demonstrated that an anti-PDGFRa polyclonal antibody frequently used in previous IHC analyses cross-reacts with PDGFRb, further confounding previous reports regarding the prevalence of PDGFRa expression in pediatric bone and soft tissue tumor patient samples (44). In light of this discordance in receptor expression between available preclinical bioresources and clinical specimens, it is difficult to investigate the full range of olaratumab activity in pediatric sarcoma in a preclinical setting and to identify potential predictive biomarkers.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, there is significant variability in the specificity of various sets of anti-PDGFR-alpha antibodies. Thus, the different antibodies used in each of the studies may have influenced the differences between the studies' results [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the expression of PDGFR in TCs or TC‐like cells in a stromal niche could simply indicate that they are spindle‐shaped MSCs that were not yet reverted toward endothelial progenitors. Moreover, aberrations in PDGFR‐α activation caused by overexpression, amplification, translocation, or point mutations of the PDGFRA gene play roles in cellular transformation (Holzer et al, ). Therefore, PDGFR‐α should be used with caution to detect specific cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…PDGFR‐α IHC is notoriously problematic, as heterogeneous results in terms of staining specificity are obtained depending on the antibodies and methods that are used. Although IHC using monoclonal antibodies shows appropriate staining in cell lines, the use of polyclonal antibodies to detect PDGFR‐α expression might lead to nonspecific detection of proteins (Holzer et al, ). Moreover, the information about antibodies targeting the same antigen varies significantly depending on the manufacturer, and the responsibility for proof of specificity lies with the purchaser (Bordeaux et al, ).…”
Section: Introductionmentioning
confidence: 99%